Striker - Skuy, David, 1963- (James Lorimer & Company Ltd., Publishers, 2013)
It's been almost a year since 13-year-old Cody was diagnosed with cancer for a tumor in his leg. No he's ready to start playing soccer again, if he can convince his mom to let him try out. Though it's a struggle, Cody makes the team as a sub. But things aren't right on the Lions, and after a team shakeup, he finds himself with more playing time than he thinks he can handle. Cody doesn't want to let his teammates down, and telling his mom will mean he'll be taken off the team. Can Cody find the strength and the courage to get his A-game back?